Quantification of Trans-Resveratrol-Loaded Solid Lipid Nanoparticles by a Validated Reverse-Phase HPLC Photodiode Array - Rigon, Roberta B. [UNESP]; Fachinetti, Naiara [UNESP]; Severino, Patricia; Durazzo, Alessandra; Lucarini, Massimo; Atanasov, Atanas G.; El Mamouni, Soukaina; Chorilli, Marlus [UNESP]; Santini, Antonello; Souto, Eliana B. (Mdpi, 2019)
A new method based on reverse-phase HPLC combined with photodiode array (PDA) was developed to quantify the release of trans-resveratrol (tRES) from solid lipid nanoparticles (SLN). The mobile phase was composed of 75:0:25 (V/V) water/methanol/acetonitrile at 0-3.5 min, 32.5:30.0:37.5 (V/V) water/methanol/acetonitrile at 3.6-5.8 min, and 75:0:25 (V/V) water/methanol/acetonitrile at 5.9-10 min. The flow rate was set at 1.0mL/min, and tRES was detected at the wavelength of 306.6 nm. A concentration range of 1-100 mu g/mL was used to obtain the linear calibration curve. SLN were produced by ultrasound technique to load 0.1% (wt/wt) of tRES, and the in vitro release of the drug was run in modified Franz diffusion cells. The mean recovery of tRES was found to be 96.84 +/- 0.32%. The intra-assay and inter-assay coefficients of variation were less than 5%. The proposed method was applied to in vitro permeability studies, and the Weibull model was found to be the one that best fits the tRES release, which is characterized by a simultaneous lipid chain relaxation and erosion during drug release.
Keywords: trans-resveratrol; nanotechnology; solid lipid nanoparticles; high-performance liquid chromatography